India’s Maneuvering in Nepal - Timalsina, Saroj Kumar (Khwopa Journal, 2024)
The author employed descriptive and analytical research methods to achieve the purpose of examining Indian excessive oversight in Nepal. The author found that India lags behind Nepal in terms of Indian maneuvering. Geo-location, an open border, socio-cultural connection, language proximity, public diplomacy, and India's participation in every political movement have defined Nepal-India relations. Although India does not promote democracy in Nepal, the country's government and administration do. To gain this possibility, Nepal must embrace unilaterally favorable accords such as Tanakpur (Mahakali), Koshi, Gandaki, and others. Since the Maoists and the SPA reached a 12-point agreement prior to the adoption of the current constitution, Indian maneuvering has wrecked Nepal's politics and government.